2020
DOI: 10.21203/rs.3.rs-19049/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of frailty in aortic valve surgery.

Abstract: Background Frailty is a geriatric syndrome that diminishes potential functional recovery after any surgical procedure. Preoperative surgical risk assessment is crucial to calibrate the risk and benefit of cardiac surgery. The aim of this study was to test usefulness of FRAIL Scale and other surgical-risk-scales and individual features of frailty. Methods: Prospective study. From May-2014 to February-2016, we collected 200 patients who underwent aortic valve replacement, either surgically or transcatheter. At 1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…21–23,32,35 Greater frailty at 6 months in 3 studies (n = 437) was also significantly associated with mortality (OR, 2.97 [95% CI, 1.54–5.72]; P < .01; I 2 = 20%; Figure 2B). 25,35,36 For 1-year mortality, 3 studies (n = 486) were pooled, and frailty based on the FRAIL scale was nonsignificantly associated with an OR of 1.54 (95% CI, 0.91–2.58; P = .11; I 2 = 0%; Figure 2C). 27,30,35…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…21–23,32,35 Greater frailty at 6 months in 3 studies (n = 437) was also significantly associated with mortality (OR, 2.97 [95% CI, 1.54–5.72]; P < .01; I 2 = 20%; Figure 2B). 25,35,36 For 1-year mortality, 3 studies (n = 486) were pooled, and frailty based on the FRAIL scale was nonsignificantly associated with an OR of 1.54 (95% CI, 0.91–2.58; P = .11; I 2 = 0%; Figure 2C). 27,30,35…”
Section: Resultsmentioning
confidence: 95%
“…A total of 18 studies with 4479 participants 21–38 were included after screening 7800 citations and 85 full-text articles (Figure 1). An additional 4 studies were found to match our inclusion and exclusion criteria 39–42 ; however, they were missing necessary data for our analysis (ie, percent frail) 39–41 or used the same population as a previously published study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations